Improving the methodical approach to formation of organizational and economic mechanisms to form and use of SMB income - Назарова, Тетяна Юріївна (Technology audit and production reserves, 2015)
An improved methodological approach for the selection of organizational and economic measures for the development and use of income are proposed in the article. Groups of financial strategies for SMB are revealed. Organizational and economic measures for forming financial strategies are established. The mechanism for positioning companies in the proposed matrix, the coordinates of which are integral indicators of financial performance, production and marketing activities is developed. Application of an improved methodological approach to the choice of organizational and economic measures for the formation and use of the profit in the practical activities of domestic enterprises allows visually detect changes in the conditions and results of management, provides the necessary information base to make effective management decisions. Methodical recommendations for the organization of the working group on the formation and use of income whose goal is the timely improvement of process management on a strategic and operational level in order to improve the profitability of its activities are developed. The use of these recommendations will enable the director and functional managers to make timely management decisions on the formation and use of income, taking into account all the peculiarities of the processes occurring in the enterprise.